2017
DOI: 10.17221/616/2017-pse
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of molybdenum availability to plants in differentiated soil conditions

Abstract: The aim of the study was to assess of plant available molybdenum (Mo) resources in the solutions of soils as well as to evaluate the effects of selected soil properties on changes of the Mo concentration in the soil solution. Sixty-two soil samples were investigated. The soil solutions were obtained by modified vacuum displacement method. The results showed that Mo concentrations in the soil solutions were much differentiated, ranging from 0.002 to approximately 0.100 µmol/L. Positive correlations were found b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…We found a significant positive relationship between soil pH and the availability of soil Mo (extracted with water and/or AB-DTPA; Table 2), suggesting that Mo availability is dependent upon soil pH. Previous studies also suggested that alkaline soils increase Mo availability [8,9,56,57]. Another study by Rutkowska et al [57] also found a significant positive correlation between Mo availability and soil pH in the soil, which further supports this interpretation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We found a significant positive relationship between soil pH and the availability of soil Mo (extracted with water and/or AB-DTPA; Table 2), suggesting that Mo availability is dependent upon soil pH. Previous studies also suggested that alkaline soils increase Mo availability [8,9,56,57]. Another study by Rutkowska et al [57] also found a significant positive correlation between Mo availability and soil pH in the soil, which further supports this interpretation.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies also suggested that alkaline soils increase Mo availability [8,9,56,57]. Another study by Rutkowska et al [57] also found a significant positive correlation between Mo availability and soil pH in the soil, which further supports this interpretation. They suggested that this relationship was mainly caused by an increase in free negative charges onto the soil colloidal surfaces, which led to electrostatic repulsion between Mo anions and soil particles [56,57].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Alkaline pH limits especially the availability of micronutrients (i.e., Cu, Fe, Mn, and Zn;Rengel, 2015) to the plants but also of some macronutrients (i.e., P; Ramírez-Rodríguez et al, 2007;Gentili et al, 2018). Among the micronutrients, the only exception is Mo, which appears to be less available at acidic pH and more available under alkaline pH (Rutkowska et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The soil at the trial sites was poor in Mo (0.12 mg kg −1 ), as agricultural soils generally range from 0.2 to 5.0 mg kg −1 (Rutkowska, Szulc, Spychaj-Fabisiak, & Pior, 2017). The soil of the 2017 trial was not analyzed for Mo content, but the site was located 265 m from the site used in 2018.…”
Section: Effects Of Seed Mo Content and Nitrogen Fertilization On Cowpea Yieldmentioning
confidence: 99%